The Brussels effect how the European Union rules the world - Bradford, Anu (Oxford University Press, 2020)
This book challenges the prevalent view that the European Union is a declining power. It argues that notwithstanding all its challenges, the EU remains an influential superpower that shapes the world in its image through a phenomenon called "the Brussels Effect." The Brussels Effect refers to the EU's unilateral power to regulate global markets. This allows the EU to often set the standards according to which products are built and business is conducted, in Europe and beyond. Without the need to resort to international institutions or seek other nations' cooperation, the EU has the ability to promulgate regulations that shape the global business environment, leading to a notable Europeanization of many important aspects of global commerce. Different from many other forms of global influence, the Brussels Effect entails that the EU does not need to impose its standards coercively on anyone-market forces alone are often sufficient to convert the EU standard into the global standard as multinational companies voluntarily extend the EU rule to govern their global operations. In this way, the EU wields significant, unique, and highly penetrating power to unilaterally transform global markets, be it through its ability to set the standards in antitrust regulation, data protection, online hate speech, consumer health and safety, or environmental protection"--